A Multi-Center Assessment of Thyroid Function Test Precision in Chemiluminescence Immunoassay (CLIA) Systems - Bhatt, Mahendra Prasad; Gyawali, P; Joshi, RK; Sharma, B; Bhatt, NP; Bhandari, S; Nagila, A (Journal of Gandaki Medical College-Nepal, 2018)
Background: Chemiluminiscence immunoassay (CLIA) is exclusively pragmatic technology for the analysis of biomarker for diagnosis of thyroid disorders. However, performance characteristics of different chemiluminescence immunoassay (CLIA) systems supplied by different manufacturers in diverse set up for thyroid function test (TFT) has not yet been studied well. Objective: Our aim is to evaluate laboratory results by assessment of the reproducibility and repeatability of TFTs in three different diagnostic set up to assure the quality of thyroid hormone assay using chemiluminescence immunoassay (CLIA) instruments: Advia Centaur CP (Siemens), Access 2 (Beckman Coulter) and Liaison (Diasorin). Materials and Methods: Among the adult male and female individuals visited for thyroid hormone assay, 51 normal individuals were selected for the study. Three aliquots of serum samples were distributed to assess the reproducibility of three different CLIA equipments operated in three diagnostic centers. Additional three aliquots of serum were analyzed weekly for TFT (fFT3, fFT4 and TSH) to check the repeatability of assay in ADVIA Centaur CP set up. Assay precision was determined by reproducibility and repeatability of test results. Results: Results of TFTs of serum samples obtained from three different interlaboratory assays using different CLIA systems have achieved good precision showing minimal variance (P>0.05) and acceptable reproducibility. Results are also precise with adequate repeatability showing minimal variance (P >0.05) obtained from the three different intra-laboratory assays in a single CLIA system using ADVIA Centaur CP by same team. Conclusion: Our study elucidates the thyroid hormone assay performance of CLIA systems in three centers, which has shown assay precision with good reproducibility and repeatability of thyroid hormone assay. Thus, the analysis of precision as an essential component of quality control is necessary to deliver precise diagnostic services.